دراسة تأثر معدل الجرعة المكافئة لانبوبة الاشعة السينية بتغير الفولتية والتيار في الهواء لدروع الكونكريت ، الجبس والالمنيوم - بهنام, نبيل جنان; مهدي, رحمن اسماعيل; نصر الله, زينب خالد (Al-Nahrain Journal of Science, 2018)
Calculations of x-ray equivalent dose rate for concrete, gypsum and aluminum shields of thicknesses (0.5-5) cm, showed progress for concrete and close results was found for gypsum and aluminum with slightly better results for gypsum in the thickness range (1-2.5)cm. Results to effect of voltage and current in air showed exponential relation between voltage and dose equivalent rate. The linear relation for tube current.